The Implementation of Picture and Picture to Enhance Elementary School Students Writing Skills - Amelia, Vita; Adiwijaya, Satria Nugraha (Universitas Pattimura, 2025)
Writing skills are an integral part of measuring learning. Moreover, the meaning of writing is centered on readability indicators that allow problems in language to be encountered. This happens because of the gap in imagination and the rules of the main idea of writing that is mastered. This study aims to determine the application of Picture and Picture learning model in improving students' writing skills conducted in Class IV of Insan Mulia Integrated Islamic Elementary School Kotagajah. This research is a type of Classroom Action Research (CAR). The data collection techniques used were observation, interview, and test. Based on the results of the analysis, it is known that after applying the Picture And Picture learning model for 2 cycles. The results of the action can be seen that there is an increase in learning activities by 16% in cycle I of 73% and cycle II of 84%. The results of students' writing skills in writing simple essays can be seen from the posttest results in cycle I with a completeness of 52% and the posttest results in cycle II amounted to 81%. This description reinforces the fact that picture and picture can be a solution to improve students' writing skills.